The black flag among others: (trans)nationalism and internationalism in the construction of anarchism in Brazil (1890-1930) - Santos, Kauan Willian (Revista Crítica Histórica, 2022)
This article, a partial result of a doctoral thesis under development by the Department of Social History at the University of São Paulo, seeks to reflect on the connection between anarchism and internationalism and the practical transnationalism, through immigration, militant networks and circulation of ideas and experiences, including the vision of the nation, nationalism, patriotism and race of its agents, as well as their overlap with their concepts and class practices. After a justification based on a theoretical debate on the topic, we suggest the division into three moments within the Brazilian republican periodical, where we observe changes, both in its practices, forms of insertion and relationship, debates and vision about its movement and the elements analyzed.